2019
DOI: 10.3390/ijerph16234626
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Work and the Risk of Spontaneous Abortion: A Systematic Review and Meta-Analysis

Abstract: (1) Background: In the semiconductor industry, female workers were identified as having an increased risk of spontaneous abortion (SA). To date, the association between semiconductor work and SA is controversial. We aimed to assess the association between semiconductor work and specific processes and SA, in the semiconductor industry. (2) Methods: A literature search was conducted using databases such as PubMed, Embase, Cochrane library, and other core databases, from the date of inception of these databases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…First, there is a lack of research on the topic. In the case of spontaneous abortion, there were only seven individual studies, including one meta-analysis [ 3 , 9 , 23 , 24 ]. In the case of cancer, there were at least two to six studies for each cancer type [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there is a lack of research on the topic. In the case of spontaneous abortion, there were only seven individual studies, including one meta-analysis [ 3 , 9 , 23 , 24 ]. In the case of cancer, there were at least two to six studies for each cancer type [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies and reviews have since described an association between semiconductor work and the increased risk of several occupational diseases [ 6 , 7 , 8 ]. A previous study also reported significant rates of spontaneous abortion in female workers [ 9 ]. However, findings from existing studies are insufficient for reaching a definitive conclusion concerning the relationship between semiconductor work and occupational disease risk.…”
Section: Introductionmentioning
confidence: 87%
“…The first epidemiological occupational study from the United Kingdom reported that the risk of cancer incidence and death were high in the semiconductor industries [ 6 ]. Since then, many studies have been conducted to assess the association between occupational exposure in the semiconductor industry and occupational diseases as a cohort or systematic review [ 7 , 8 , 9 , 10 ]. However, it was difficult to assess causality because of the controversy between the studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s, as an occupational disease, the risk of spontaneous abortion among semiconductor workers was first reported [1]. Since then, research about workers' health problems, such as cancers, reproductive hazards, etc., and hazardous substances or detailed semiconductor processes that cause health effects in workplaces have been published [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%